The design and simulation of a planar microarray dot electrode for a dielectrophoretic lab-on-chip device - Yafouz, Bashar; Kadri, Nahrizul Adib; Ibrahim, Fatimah (Electrochemical Science Group, 2012)
Dielectrophoresis (DEP) has been proven as a method of manipulating and analyzing the electrophysiological properties of bioparticles by applying non-uniform electric fields generated through special electrodes. Various electrode geometries have been developed to address different applications. Electric field simulation over electrodes is essential in order to optimize the generated DEP force for cell manipulation. This paper describes the study of electric field distribution over planar multiple microarray dot electrodes using numerical modeling of Comsol Multiphysics 4.2aÂ®. Electric field evaluation for different dot sizes has been demonstrated by applying a range of frequencies to the designed electrodes. Results show that the electric field is axisymmetrical around the center of the dot aperture and that it is higher at the dot edges than the dot centers. Furthermore, adding ground plane between adjacent dots increases the electric field strength. Â© 2012 by ESG.